Pelatihan Pemasaran Digital UMKM: Memperluas Pasar Sale Pisang Khas Majenang - Widya Pratiwi; Ahmad Arifin Zain; Nur Moniroh (Politeknik Negeri Batam, 2026)
This training is designed to assist Micro, Small, and Medium Enterprises (MSMEs) in enhancing their product marketing capacity through digital strategies. The main focus of the program is on Majenang’s local specialty product, sale pisang, which has a broad market potential but is still limited in its utilization of digital technology. The training covers topics from basic concepts to hands-on practice involving social media, online marketplaces, content optimization, and effective online promotion strategies. Mentoring is conducted using a direct coaching and field practice approach, where participants are guided to create promotional content, manage social media accounts and online stores, and implement digital marketing strategies according to their target markets. The results of the mentoring are presented through participant presentations, showcasing the digital strategies they have applied. Evaluations indicate that 90% of participants are able to manage social media accounts and online stores independently, 75% have successfully expanded their market reach beyond their local area, and 60% have experienced a sales increase of 20–50% after the mentoring. With this interactive and practice-based method, the training not only improves participants’ understanding of digital marketing but also strengthens the brand of Majenang’s sale pisang, thereby making a tangible contribution to MSME development and enhancing the competitiveness of local products in the digital era